THE INFLUENCE OF MONOTHERAPY WITH ENAM ON THE OVERALL CORONARY RISK: DYNAMICS OF CORRECTABLE CARDIOVASCULAR RISK FACTORS IN PATIENTS WITH METABOLIC SYNDROME - M. N. Mamedov; O. V. Kosmatova; L. A. Hadipash; N. V. Kiseleva; R. G. Oganov (Российский кардиологический журнал)
The influence of monotherapy with enam on the overall coronary risk: dynamics of correctable cardiovascular risk factors in patients with metabolic syndrome.